DISTRIBUSI DAN KEMELIMPAHAN PLANKTON DI WET DUNE SLACKS GUMUK PASIR PARANGTRITIS, BANTUL, DIY. - Mawarni, Annisa; Hadisusanto, Hadisusanto; Suwarno, Suwarno (Biospecies, 2019)
Plankton community has an important role in the food chain, nutrient cycle and initial succession process in the wet dune slacks. Wet dune slacks are damp or wet hollows left between dunes where have a seasonally fluctuating water table. This unique habitat has been protected in European, but in Indonesia has not been studied by researchers. The aim of this research is to study plankton distribution and abundance in wet dune slacks with physico-chemical factors that most influence. Sample was picked on February 2018 in Gumuk Pasir Parangtritis, Bantul, Daerah Istimewa Yogyakarta. There was 10 liters sample taken using bucket with 3 replications in 5 different wet dune slacks. Water sample was filtered using plankton-net 120 mesh size and physico-chemical parameters was measured. The results of plankton samples show there were 37 species of pennate diatoms, 1 species of centric diatoms, 23 species of algae unisel, 28 species of algae colony, 18 species of algae filaments, 3 species of dinoflagellates, 6 species of chlorophyll protozoa, 22 species of rotifers, 6 species of cladocera, 11 species of ostracoda, 5 species of copepods, and 5 species of protozoa. Plankton species that have succeeded in wet dune slacks are species that have a strategy of surviving in the extreme habitat by changing to resting stages, cysts, spores, and resting eggs. Phytoplankton species that dominated in the wet dune slacks was Cyclotella meneghiniana while for zooplankton was Chlamydotheca flexilis and Alona rectangula. Phytoplankton distribution and abundance was regulated by wind speed, C-organic content, alkalinity, light intensity, phosphate content, pH and dissolved oxygen. The physico-chemical factors that most influence the distribution and abundance of zooplankton was concentration of dissolved oxygen, dissolved CO2, pH, water temperature, air temperature, depth, water transparency, wind speed, light intensity, C-organic content, sulfate and phosphate content.